Schumpeter School International Comparative Institutions Database - Sonja Jovicic (University of Wuppertal, Schumpeter School of Business and Economics, 2015)
For our international comparative research on the impact of institutions on economic trends, we put together the Schumpeter School International Comparative Institutions Database.1 The database comprises the panel data set on various indicators of employment, inequality and labor market institutions in twenty-one OECD countries during the time period 1970-2013. Countries included in the dataset are Australia, Austria, Belgium, Canada, Denmark, Finland, France, Germany, Greece, Ireland, Italy, Japan, Luxembourg, Netherlands, Norway, New Zealand, Portugal, Spain, Sweden, the United Kingdom and the United States. The Schumpeter School International Comparative Institutions Database is available as an Excel or Stata file upon request.
urn:nbn:de:hbz:468-20150113-111135-9
Keywords: 330